2021
DOI: 10.34172/bi.2021.22143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking, molecular dynamics simulation, and ADMET analysis of levamisole derivatives against the SARS-CoV-2 main protease (MPro)

Abstract: Introduction: The new species of coronaviruses (CoVs), SARS-CoV-2, was reported as responsible for an outbreak of respiratory disease. Scientists and researchers are endeavoring to develop new approaches for the effective treatment against of the COVID-19 disease. There are no finally targeted antiviral agents able to inhibit the SARS-CoV-2 at present. Therefore, it is of interest to investigate the potential uses of levamisole derivatives, which are reported to be antiviral agents targeting the influenza viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, during therapy, there was a nonsignificant alteration in dyspnea, cough, diarrhea, nausea, vomiting, sore throat, hyposmia, dysgeusia, and anorexia compared to the control group [99] . Interestingly, levamisole derivatives could be used as the main drug for COVID-19 treatment because they contain the molecule N°6 structure in levamisole, which could be further developed to stop the COVID-19 pandemic [100] . Altogether, it can be concluded that levamisole and its derivatives can be used in the future as antiviral drugs.…”
Section: Resultsmentioning
confidence: 99%
“…However, during therapy, there was a nonsignificant alteration in dyspnea, cough, diarrhea, nausea, vomiting, sore throat, hyposmia, dysgeusia, and anorexia compared to the control group [99] . Interestingly, levamisole derivatives could be used as the main drug for COVID-19 treatment because they contain the molecule N°6 structure in levamisole, which could be further developed to stop the COVID-19 pandemic [100] . Altogether, it can be concluded that levamisole and its derivatives can be used in the future as antiviral drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking was used to study the interaction of active compounds of Algerian plants with the Sars-Cov-2 protease target [ 11 , 12 ]. The target proteins are major (6WTT and 6LU7) proteases of the Sars-CoV-2 virus.…”
Section: Methodsmentioning
confidence: 99%
“…Other attempts against MPro were done [ 130 , 131 , 132 , 133 ] but require further experimental data to validate the hypothesis. The RNA polymerase, [ 134 ] as well as the nucleocapsid, [ 135 ] and envelope protein [ 136 ] were proposed as a druggable target, but these studies will require further confirmation by experimental data to verify whether NSPs could be considered viable targets.…”
Section: Molecular Dynamics Insights On New Sars‐cov‐2 Variantsmentioning
confidence: 99%